Responsabilidad civil por la prestación del servicio médico, a la luz de la nueva regulación de protección al consumidor - Giraldo Gómez, Luis Felipe (2023)
Law 1480 of 2011, also know as the Consumer Statute, regulates the obligations that may arise and be framed within the context of a consumer relationship. This new law also applies to the field of services, covering even the services that by their nature involve a duty of best efforts, such as the provision of medical services. All of this invites reflection on the extent and manner of application of this new regulation in the field of civil liability for the provision of medical services and, especially, if it is possible to apply in these cases the figures of statutory guarantee and responsibility for defective products that are inherent in consumer law.